Effect of fluoride ions on the structure and electrocatalytic properties of titanium dioxide nanotubes - Maltanava, Hanna M.; Poznyak, Sergey K.; Scharnagl, Nico; Ivanovskaya, Maria I.; Gaevskaya, Tatiana V. (Journal of the Belarusian State University. Chemistry, 2017)
Effect of fluoride ions on the structure of titanium dioxide films prepared by anodization has been studied usingX-ray photoelectron spectroscopy, X-ray analysis and scanning electron microscopy. Under the action of fluoride ions,tubular nanostructure of the TiO2 films was found to be destroyed at annealing in the limited mass transfer conditions.The mechanism of the processes is proposed. Fluoride doping of titanium dioxide leads to lowering the overvoltage of theoxygen electroreduction reaction on the TiO2 electrodes.
Keywords: titanium dioxide; nanotubes; doping; fluoride; oxygen electroreduction